MAQÂŞID ASY- SYARI’AH : PERLINDUNGAN ANAK DIFABEL PADA YAYASAN SAYAP IBU, YOGYAKARTA - Wahdin, Muhammad Khoirul (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2015)
Ideally every child has his or her own father and mother who carry out their roles responsibly. However, in reality there are a number of children with disabilities who are ignored by their parent and consecutively taken care, nurtured, and guided by Yayasan Sayap Ibu. In order to protect the children, the caretaker of Yayasan Sayap Ibu deploys following efforts: preserving mind or intellect through education, preserving lineage (nasab) through nurturing and caretaking, and protecting property through many aids allocated to fulfill children needs. In sum, the article tries to examine whether the protection provided by Yayasan Sayap Ibu is in line with the theory of maqâsid asy-syari’ah or not. The theory consists of five pillars as follow: hifz din (protection toward religion), hifz nafs (protection toward soul), hifz aql (protection toward mind), hifz nasl (preserving toward lineage) dan hifz mal (protection toward property.